2010
DOI: 10.1105/tpc.110.076257
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisVILLIN5, an Actin Filament Bundling and Severing Protein, Is Necessary for Normal Pollen Tube Growth

Abstract: A dynamic actin cytoskeleton is essential for pollen germination and tube growth. However, the molecular mechanisms underlying the organization and turnover of the actin cytoskeleton in pollen remain poorly understood. Villin plays a key role in the formation of higher-order structures from actin filaments and in the regulation of actin dynamics in eukaryotic cells. It belongs to the villin/gelsolin/fragmin superfamily of actin binding proteins and is composed of six gelsolin-homology domains at its core and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
202
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(206 citation statements)
references
References 75 publications
4
202
0
Order By: Relevance
“…It is not clear whether a stepwise assembly mechanism also applies to assembly of actin cables in the pollen tube. If this model holds true, FIM5 may function to tighten actin cables initiated by pollen-expressed villins, such as VLN5 (Zhang et al, 2010), VLN2, or VLN1 (Honys and Twell, 2003;Pina et al, 2005). Based on these observations, it is reasonable to propose that loss of function of FIM5 may induce a defect at the step of tightening actin cables initiated by villins, leading to the appearance of thicker actin cables.…”
Section: Fim5 Is Required For the Organization Of Actin Filaments In mentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear whether a stepwise assembly mechanism also applies to assembly of actin cables in the pollen tube. If this model holds true, FIM5 may function to tighten actin cables initiated by pollen-expressed villins, such as VLN5 (Zhang et al, 2010), VLN2, or VLN1 (Honys and Twell, 2003;Pina et al, 2005). Based on these observations, it is reasonable to propose that loss of function of FIM5 may induce a defect at the step of tightening actin cables initiated by villins, leading to the appearance of thicker actin cables.…”
Section: Fim5 Is Required For the Organization Of Actin Filaments In mentioning
confidence: 99%
“…Loss of FIM5 function may lead to functional substitution of other bundling factors, such as other pollen-expressed fimbrin isoforms (FIM4 and FIM3; Pina et al, 2005), villins (VLN5 [Zhang et al, 2010], VLN2, and VLN1 [Pina et al, 2005]), or LIM domaincontaining proteins (Wang et al, 2008;Thomas et al, 2009). Actin cables formed in the presence of these other factors could have longer distances between adjacent actin filaments.…”
Section: Fim5 Is Required For the Organization Of Actin Filaments In mentioning
confidence: 99%
“…It was reported that increase of calcium concentration results in destabilization and depolymerization of actin. 18 However, Fan et al found that the cytoplasmic concentration of calcium decreased in cadmium-treated Arabidopsis root hairs. 15 Therefore it is possible that that cadmium might mimic calcium to activate actin filament-severing proteins and thus lead to actin filaments depolymerization.…”
Section: Cadmium and Cytoskeletonmentioning
confidence: 99%
“…Additionally, many actin-bundling/ cross-linking factors that maintain normal pollen germination and pollen tube growth have been identified in Arabidopsis pollen. For example, a VLN5 loss-of-function mutant displays delayed pollen tube growth and results in F-actin in both pollen grains and pollen tubes that are sensitive to latrunculin B (Lat B) (7). A loss-of-function mutant of Arabidopsis FIMBRIN5 also results in delayed pollen germination and inhibited tube growth, with both pollen germination and tube growth being hypersensitive to Lat B (13).…”
mentioning
confidence: 99%